New York’ta Beş Minare ve Mucize Filmine Göstergebilimsel Bir Bakış - Kutbay, Arsen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Starting with the very the first fictional script Le Voyage Dans La Lune (Aya Yolculuk) in which chain of events forms the basis of expressions, modern cinema expressed itself in many ways from the day Le Voyage Dans La Lune recorded -1902- until today. Although there are various narrative forms, semiotics is the cornerstone of the fictional style. And the cornerstones of semiotics are of course the indicators. In this research the aim is to examine how the visual and the auditory indicators are used to reinforce the meaning of the plot in a fictional movie and its importance to the cinema. In this context, besides the indicators that directly affect the audience, it has a very rich content with implicit indicators, New York’ta Beş Minare (Five Minarets in New York) and Mucize (The Miracle) that are directed by Mahsun Kırmızıgül, have been identified as the universe of the research and semiotics were used as methods. In this context, the analysis of the related films was carried out using the symbol-icon-sign triangle which is the semiotic model of Pierce. The scenes that are subjected to analysis were chosen through purposeful sampling. As a result of the research, from the evaluation of the main findings and of course the reason that the fiction films are based on an effort to create representations of reality from the cross-sections of everyday life, it is emphasized that these realities are meaningful and the importance of making use of the indicators frequently present in daily life is emphasized in the cinema. In this context, the representation of reality in cinema; reinforcing the narrative of time, space and plot, it is concluded that semiotics is an unshakable component in the art of cinema in terms of the transfer of emotions and messages to be given. In the scope of the research, the problematic, aim, question, importance and the limitations of the research are presented in the introduction part of this thesis. In the second part, the relationship between semiotics and cinema is presented. In the third section, the method applied in the research is explained and the fourth part includes semiotic analysis of Five Minarets in New York and The Miracle that are directed by Mahsun Kırmızıgül. In the fifth section, the main findings of the analysis are evaluated for the purpose of the research. Keywords: Semiotics, Indicator Usage in Cinema, Visual and Auditory Indicators, Five Minarets in New York, The Miracle

ÖZ: Olay örgüsünün anlatının temelini oluşturduğu, ilk senaryolu kurmaca film olan Le Voyage Dans La Lune ( Aya Yolculuk)’un 1902 yılında çekilmesinden bugüne, modern sinema pek çok anlatım biçimiyle kendisini ifade etmektedir. Nitekim bu anlatım biçimleri içerisinde kurgusal anlamda üslubun temel taşını ise göstergebilim oluşturmaktadır. Göstergebilimin temel taşları da pek tabii göstergelerdir. Bu araştırma ise; kurmaca bir filmde görsel ve işitsel göstergelerin olay örgüsüyle anlatılmak istenen anlamı pekiştirme noktasında nasıl kullanıldığını ve bunun sinemadaki önemini irdelemeyi amaç edinmiştir. Bu kapsamda izleyiciye direkt etki eden göstergelerin yanı sıra, örtük göstergelerle de oldukça zengin bir içeriği bulunan, Mahsun Kırmızıgül’ün yönetmenliğini yaptığı New York’ta Beş Minare ve Mucize adlı filmler araştırmanın evreni olarak belirlenmiş olup, göstergebilim ise yöntem olarak kullanılmıştır. Bu kapsamda ilgli filmlerin analizi, Pierce’ın göstergebilimsel modeli olan sembol-ikon-belirtke üçgeni kullanılarak gerçekleştirilmiştir. Analize tabi tutulan sahneler ise, amaçlı örneklem kullanılarak seçilmiştir. Araştırma sonucunda ise, elde edilen temel bulgu değerlendirmesinde; kurmaca filmlerin gündelik hayatın kesitlerinden gerçeklik temsilleri yaratma çabasından mütevellit, yine bu gerçeklikelerin anlamlandırıldığı ve gündelik hayatın içerisinde sıklıkla var olan göstergelerden yararlanılmasının sinemadaki önemi vurgulanmıştır. Bu bağlamda sinemada gerçeklik temsili; zaman, mekan, olay örgüsü anlatısının pekiştrilmesi, duyguların ve verilmek istenen iletilerin aktarımları açısından sinema sanatında göstergebilimin sarsılmaz bir bileşen olduğu sonucu varılmıştır. Araştırma kapsamda bu tezin giriş bölümünde ilkin araştırmanın sorunsalı, amacı, sorusu, önemi ve sınırlılıkarı serimlenmektedir. İkinci bölümde ise göstergebilim ve sinema bağıntısı ortaya konulmuştur. Üçüncü bölümde araştırmada uygulanan yöntem açımlanırken, dördüncü bölüm ise, Mahsun Kırmızıgül’ün yönetmenliğini yaptığı New York’ta Beş Minare ve Mucize filmlerinin göstergebilimsel analizini kapsamaktadır. Beşinci bölümde ise, yapılan analizden çıkarılan temel bulgu üzerine araştırmanın amacına yönelik değerlendirme yapılmıştır. Anahtar Kelimeler: Göstergebilim, Sinemada Gösterge Kullanımı, Görsel ve İşitsel Göstergeler, New York’ta Beş Minare, Mucize
İletişim ve Medya Çalışmaları Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, İletişim Fakültesi, 2019. Tez Danışmanı: Yard. Doç. Dr. Aysu Arsoy.
Keywords: New York’ta Beş Minare--Film Inceleme; Göstergebilim; Sinemada Gösterge Kullanımı; Görsel ve İşitsel Göstergeler; New York’ta Beş Minare; Mucize; Semiotics; Indicator Usage in Cinema; Visual and Auditory Indicators; Five Minarets in New York; The Miracle